A national patient and public colorectal research agenda: integration of consumer perspectives in bowel disease through early consultation. (January 2017) - McNair, A. G. K.; Heywood, N.; Tiernan, J.; Verjee, A.; Bach, S. P.; Fearnhead, N. S.; ,
Abstract: Aim: There is a recognized need to include the views of patients and the public in prioritizing health research. This study aimed: (i) to explore patients' views on colorectal research; and (ii) to prioritize research topics with patients and the public. Method: In phase 1, 12 charitable organizations and patient groups with an interest in bowel disease were invited to attend a consultation exercise. Participants were briefed on 25 colorectal research topics prioritized by members of the Association of Coloproctology of Great Britain and Ireland. Focus groups were conducted and discussions were recorded with field notes. Analysis was conducted using principles of thematic analysis. In phase 2, a free public consultation was undertaken. Participants were recruited from newspaper advertisements, were briefed on the same research topics and were asked to rate the importance of each on a five‐point Likert scale. Descriptive statistics were used to rank the topics. Univariable linear regression compared recorded demographic details with mean topic scores. Results: Focus groups were attended by 12 patients who highlighted the importance of patient‐centred information for trial recruitment and when selecting outcome measures. Some 360 people attended the public consultation, of whom 277 (77%) were recruited. Participants rated 'What is the best way to treat early cancer in the back passage?' highest, with 227 (85%) scoring it 4 or 5. There was no correlation between participant demographics and mean topic scores. Conclusion: The present study prioritized a colorectal research agenda with the input of patients and the public. Further research is required to translate this agenda into real improvements in patient care.